Transparansi dan Akuntabilitas dalam Pengelolaan Dana Masjid Mandiri: Studi Kasus Masjid Kota Medan - Sabaruddin Chaniago; Nurlaila Nurlaila; Mustapa Khamal Rokan (Society, 2024)
This study examines the level of transparency in the management of independent mosque funds in Medan City, North Sumatra, Indonesia, evaluates adherence to accountability principles, and provides actionable recommendations for improvement. Using a quantitative research approach, questionnaires and observations were used to collect data from mosque administrators, worshippers, and donors at the Al-Musabbihin Mosque. These instruments were designed to assess trust and participation in mosque activities. Data analysis was conducted using Structural Equation Modeling (SEM) with Smart PLS 3.0, focusing on Outer and Inner Model evaluations. The results reveal that human resource (HR) competency, internal control systems, technological integration, stakeholder engagement, and compliance with financial management standards significantly impact transparency and accountability in mosque fund management. Additionally, organizational commitment amplifies the positive influence of HR competency and internal controls on these outcomes. The study highlights the critical need for ongoing HR development through targeted training and education to ensure effective and accountable fund management. Furthermore, establishing comprehensive internal control systems is essential to prevent fund misuse and build public trust. The findings demonstrate that transparent and accountable fund management fosters public confidence, optimizes resource utilization, and enhances the mosque’s capacity as a vibrant and empowered social institution.